Identification of a VxP Targeting Signal in the Flagellar Na+/K+‐ATPase. (13th October 2015) - Laird, Joseph G.; Pan, Yuan; Modestou, Modestos; Yamaguchi, David M.; Song, Hongman; Sokolov, Maxim; Baker, Sheila A.
Abstract : Na + /K + ‐ATPase (NKA) participates in setting electrochemical gradients, cardiotonic steroid signaling and cellular adhesion. Distinct isoforms of NKA are found in different tissues and subcellular localization patterns. For example, NKA α1 is widely expressed, NKA α3 is enriched in neurons and NKA α4 is a testes‐specific isoform found in sperm flagella. In some tissues, ankyrin, a key component of the membrane cytoskeleton, can regulate the trafficking of NKA. In the retina, NKA and ankyrin‐B are expressed in multiple cell types and immunostaining for each is striking in the synaptic layers. Labeling for NKA is also prominent along the inner segment plasma membrane (ISPM) of photoreceptors. NKA co‐immunoprecipitates with ankyrin‐B, but on a subcellular level colocalization of these two proteins varies dependent on the cell type. We used transgenic Xenopus laevis tadpoles to evaluate the subcellular trafficking of NKA in photoreceptors. GFP‐NKA α3 and α1 are localized to the ISPM, but α4 is localized to outer segments (OSs). We identified a VxP motif responsible for the OS targeting by using a series of chimeric and mutant NKA constructs. This motif is similar to previously identified ciliary targeting motifs. Given the structural similarities between OSs and flagella, our findings shed light on the subcellular targeting of this testes‐specific NKA isoform. Abstract : Na + /K + ‐ATPase (NKA) is the enzyme critical for maintaining the electrochemical gradient across cellular membranes. The subcellular localization of NKA can vary widely in different cell types, but it is not known how this is accomplished. Here we use transgenic frog photoreceptors as a model to probe this question. By comparing the differential localization of two NKA subunits, α3 versus α4, we discovered a VxP motif that we found in NKA α4 is required for localization to the ciliary compartment of photoreceptors. NKA α3, which lacks this motif, is instead localized to the inner segment compartment of photoreceptors.